2018
DOI: 10.1017/s0016756818000122
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon geochronology and geochemistry of Jurassic sandstones in the Xiongcun district, southern Lhasa subterrane, Tibet, China: implications for provenance and tectonic setting

Abstract: Jurassic sandstones in the Xiongcun porphyry copper–gold district, southern Lhasa subterrane, Tibet, China were analysed for petrography, major oxides and trace elements, as well as detrital zircon U–Pb and Hf isotopes, to infer their depositional age, provenance, intensity of source-rock palaeo-weathering and depositional tectonic setting. This new information provides important evidence to constrain the tectonic evolution of the southern Lhasa subterrane during the Late Triassic – Jurassic period. The sandst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 106 publications
(236 reference statements)
0
12
0
Order By: Relevance
“…In the southern Lhasa terrane, the subduction-related Xiongcun porphyry Cu deposit with ore-bearing country rocks of the Early-Middle Jurassic Xiongcun Formation volcano-sedimentary sequence was developed to the west of the Yeba Formation (Lang et al, 2014(Lang et al, , 2018Tafti et al, 2009;Tang et al, 2015). Sillitoe (1998) favored the compressional regime for the formation of subduction-related porphyry Cu deposits in terms of the statistic study on global Cu deposits; however, no Cu deposits have been found in the Yeba Formation, which was previously considered to be formed in continental arc setting (Zhu et al, 2008 suggests a tropical climate (Lang et al, 2018). The Yeba sandstones, however, are predominated by recycled quartz and underwent high chemical weathering, indicating that they were gradually deposited in the basin with relatively subdued uplift and low elevations (Fig.…”
Section: Two-component Mixing Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the southern Lhasa terrane, the subduction-related Xiongcun porphyry Cu deposit with ore-bearing country rocks of the Early-Middle Jurassic Xiongcun Formation volcano-sedimentary sequence was developed to the west of the Yeba Formation (Lang et al, 2014(Lang et al, , 2018Tafti et al, 2009;Tang et al, 2015). Sillitoe (1998) favored the compressional regime for the formation of subduction-related porphyry Cu deposits in terms of the statistic study on global Cu deposits; however, no Cu deposits have been found in the Yeba Formation, which was previously considered to be formed in continental arc setting (Zhu et al, 2008 suggests a tropical climate (Lang et al, 2018). The Yeba sandstones, however, are predominated by recycled quartz and underwent high chemical weathering, indicating that they were gradually deposited in the basin with relatively subdued uplift and low elevations (Fig.…”
Section: Two-component Mixing Modelmentioning
confidence: 99%
“…The Q-F-L ternary plot (Dickinson, 1985) showing clastic composition of samples from the Yeba, Xiongcun, Chumulong and Shexing Formations. The Xiongcun Formation data are from Lang et al, (2018). Q, quartz; F, feldspars; L, lithic fragments; RO, recycled orogen; UMA, undissected magmatic arc; TMA, transitional magmatic arc; DMA, dissected magmatic arc; BU, basement uplift; TC, transitional continental; CI, craton interior.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…245 Ma in the SL (X. X. Ma et al, 2020, and references therein;, and a middle Triassic-early Jurassic island arc system is within the Neo-Tethys (Lang, Liu, et al, 2019;X. X. Ma, Meert, et al, 2019;X.…”
Section: 1029/2020tc006237mentioning
confidence: 99%
“…The central Lhasa subterrane retains the most complete sedimentary record in the region and consists of Carboniferous‐Permian and late Jurassic‐early Cretaceous volcano‐sedimentary sequences, with minor Ordovician, Silurian, and Triassic limestones and rare Precambrian strata (Figure 2; e.g., Kapp et al, 2007; Zhu et al, 2013; Zhu, Zhao, Niu, Mo, et al, 2011, and references therein), which signal the presence of a Precambrian basement in the central subterrane. The southern Lhasa subterrane is dominated by the voluminous Cretaceous‐Eocene Gangdese batholith and the Paleogene Linzizong volcanic succession, with minor middle Triassic‐middle Jurassic volcano‐sedimentary sequences and intrusions (Figure 2; Lang et al, 2020; Lang, Liu, et al, 2019; Lang, Wang, et al, 2019; X. H. Wang, Lang, et al, 2019; Zhu et al, 2013; Zhu, Zhao, Niu, Mo, et al, 2011). However, some Paleozoic and Paleo‐ and Meso‐Proterozoic magmatic rocks have recently been found in this subterrane (Figure 2; Ji et al, 2012; Dong, Zhang, Geng, et al, 2010; Dong et al, 2014; Dong, Zhang, & Santosh, 2010; Lin et al, 2013; L. Ma, Kerr, et al, 2019), which suggests that the southern Lhasa subterrane is an ancient microcontinent that underwent extensive Phanerozoic crustal reworking and growth rather than a Mesozoic‐Paleogene juvenile accretionary arc terrane (L. Ma, Kerr, et al, 2019).…”
Section: Geological Backgroundmentioning
confidence: 99%